P04.05 High prevalence of rectal gonorrhoea among men reporting contact with men with gonorrhoea: implications for epidemiological treatment. (13th September 2015) - Dutt, K; Chow, EPF; Huffam, S; Klassen, K; Fairley, CK; Bradshaw, CS; Denham, I; Chen, MY
Abstract : Introduction: This study aimed to determine the prevalence of gonorrhoea and factors associated with rectal gonorrhoea among men reporting sexual contact with men with gonorrhoea. Methods: Men who presented to Melbourne Sexual Health Centre reporting sexual contact with a male with gonorrhoea were prospectively identified between March 2011 and December 2013. These men were screened for pharyngeal and rectal gonorrhoea using culture. The prevalence of gonorrhoea among contacts was compared to that among all men who have sex with men (MSM) screened at the clinic over the same period. Logistic regression was performed on demographic and behavioural characteristics to determine the predictors of infection among contacts. Results: Among 363 contacts of gonorrhoea the prevalence of rectal gonorrhoea was 26.4% (95% CI: 21.8%–31.0%) compared to 3.9% (95% CI: 3.7%–4.2%) among clinic attendees (p < 0.001). The prevalence of pharyngeal gonorrhoea among contacts was 9.4% (95% CI: 6.4%–12.4%) compared to 2.1% (95% CI: 1.9%–2.4%) among clinic attendees (p < 0.001). Among contacts who reported not always using condoms during receptive anal sex with casual partners, rectal gonorrhoea was cultured in 42.4% compared with 12.7% among contacts reporting no receptive anal sex (p < 0.001) and 20.2% among those reporting always using condoms (p < 0.001). On multivariate analysis rectal gonorrhoea was associated with inconsistent condom use during receptive anal sex with casual partners (adjusted odds ratio (AOR): 4.16; 95% CI: 1.87–9.26) and a reported past history of gonorrhoea (AOR: 1.77; 95% CI: 1.01–3.14). Conclusion: The high proportion of positive cases of gonorrhoea among contacts in this study supports epidemiological treatment of MSM presenting as contacts of gonorrhoea. Disclosure of interest: There are no conflicts of interest to be disclosed relating to this paper.